2009
DOI: 10.1038/emboj.2009.32
|View full text |Cite
|
Sign up to set email alerts
|

ASK1 and ASK2 differentially regulate the counteracting roles of apoptosis and inflammation in tumorigenesis

Abstract: Apoptosis and inflammation generally exert opposite effects on tumorigenesis: apoptosis serves as a barrier to tumour initiation, whereas inflammation promotes tumorigenesis. Although both events are induced by various common stressors, relatively little is known about the stress-induced signalling pathways regulating these events in tumorigenesis. Here, we show that stress-activated MAP3Ks, ASK1 and ASK2, which are involved in cellular responses to various stressors such as reactive oxygen species, differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
110
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 120 publications
(118 citation statements)
references
References 39 publications
(60 reference statements)
8
110
0
Order By: Relevance
“…Indeed, several in vivo analyses revealed that ASK1 is a critical regulator of apoptosis in liver, heart, and nerve tissue and a regulator of inflammation in the skin and colon (10)(11)(12)(13)32). This study showed that the expression of ASK1 was elevated in human GC tissue.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Indeed, several in vivo analyses revealed that ASK1 is a critical regulator of apoptosis in liver, heart, and nerve tissue and a regulator of inflammation in the skin and colon (10)(11)(12)(13)32). This study showed that the expression of ASK1 was elevated in human GC tissue.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, ASK1 affects multiple cellular functions, including survival, differentiation, and the innate immune response (5,7,8) and has been reported to be involved in the pathogenesis of various human diseases, including neurodegenerative (9), cardiovascular (10), and inflammatory diseases (11,12). Additionally, ASK1 has been shown to participate in both colon (12) and skin (13) tumorigenesis through the regulation of inflammation and apoptosis. However, no reported study has demonstrated a role for ASK1 in gastric tumorigenesis.…”
Section: Jnk | C-junmentioning
confidence: 99%
“…Different from the expression pattern of ASK1 or ASK2 (ref. 24), ASK3 was predominantly detected in the kidney by realtime quantitative PCR analysis ( Fig. 1c) and immunoblot analysis probed with an ASK3-specific antibody ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…15 There was only one methylated (>33%) locus shared between any of the mouse medulloblastoma tumors and the patient sample. Common to SmoA2 and the patient sample was FAM83F (family with sequence similarity 83, member F), a gene of unknown function.…”
Section: Mouse Models Of Medulloblastoma Lack Extensive Promoter Cpg mentioning
confidence: 99%